2013
DOI: 10.1021/np300773x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antiplasmodial Constituents of Beilschmiedia cryptocaryoides

Abstract: Four new beilschmiedic acid derivatives, cryptobeilic acids A-D (1-4), and tsangibeilin B (5) have been isolated from the bark of Beilschmiedia cryptocaryoides collected from Madagascar. Their structures were elucidated using detailed spectroscopic and spectrometric methods. Cryptobeilic acid A (1) and tsangibeilin B (5) structures were confirmed by single-crystal X-ray diffraction analysis. Compounds 1-5 displayed moderate antibacterial activity against Escherichia coli 6r3, Acinetobacter calcoaceticus DSM 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…These compounds were reported to be active against clinical isolate of methicillin-resistant Staphylococcus aureus (26). Cryptobeilic acid A and cryptobeilic acid B isolated from B. cryptocaryoides have showed antibacterial activity against Escherichia coli, Acinetobacter calcoaceticus and Pseudonamas stutzeri (7). Pipyahyine, an amide isolated from B. zenkeri showed moderate activity against Bacillus subtilis and Pseudomonas agarici, while a flavonoid, beilschmieflavonoid B showed weak activity against Streptococcus minor (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds were reported to be active against clinical isolate of methicillin-resistant Staphylococcus aureus (26). Cryptobeilic acid A and cryptobeilic acid B isolated from B. cryptocaryoides have showed antibacterial activity against Escherichia coli, Acinetobacter calcoaceticus and Pseudonamas stutzeri (7). Pipyahyine, an amide isolated from B. zenkeri showed moderate activity against Bacillus subtilis and Pseudomonas agarici, while a flavonoid, beilschmieflavonoid B showed weak activity against Streptococcus minor (23).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the leaves of B. tonkinensis are used by the Indonesians and Malays as bandages for broken bones (6). In Madagascar, B. cryptocaryoides the fruit, bark, and leaf are utilized by the locals for treatment of contagious disease and malaria (7). Reports on several bioactivities of Beilschmiedia species have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Talontsi et al [21] and a co-worker identified cryptobeilic acids A-D, tested for anti-bacterial activity and showed that cryptobeilic acid A gave moderate activity against Escherichia coli (MIC value of 10 μM), while cryptobeilic acid B was active against Pseudonamas stutzeri with a MIC value of 10 μM. In another study, Chouna et al [44] reported that beilschmiedic acid C demonstrated the best activity against Bacillus subtilis and Micrococcus luteus with MIC of 89.5, 5.58 and 11.1 µM, respectively.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The other compounds which showed remarkable activity were pipyahyine and betulinic acid which gave IC 50 values of 3.7 and 5.2 µM, respectively. Talontsi et al [21] studied the anti-plasmodial activity of the isolated endiandric acid derivatives from B. cryptocaryoides. Cryptobeilic acid B exhibited anti-plasmodial activity against the erythrocytic stages of chloroquine-resistant Plasmodium falciparum strain NF54, followed by tsangibeilin B and cryptobeilic acid D at a concentration of 10 μg/mL.…”
Section: Anti-plasmodial Activitymentioning
confidence: 99%
See 1 more Smart Citation